Metoda projektów jako strategia postępowania dydaktycznego na wyższej uczelni. O efektach kształcenia i metodzie projektów - Zając, Bożena (Wydawnictwo Naukowe UAM, 2015)
The article is an attempt to present the project method as a training strategy used at Polish universities, elevating the quality of students training through such training process organisation that will correspond with students’ expectations, their capabilities and predispositions. Implementing the project method in university educational practice will allow, in accordance with the applicable National Qualifications Framework, achievement of training effects in all categories: knowledge, skills and social competences. The article clearly states the role of students and the role of university teachers. It gives students the ability to initiate, explore and develop their own interests, learning by doing and experience. Students take responsibility for their own work, they define their own goals, direct themselves and evaluate their achievements themselves. Accordingly, the role of a university teacher using the project method in the process of educating students ceases to be that of only an expert in his field and a ‘knowledge feeder’. His role is, first of all, to create working conditions for students, motivate and accompany them in the learning process. In addition, the article provides information about the history and the present of the project method, pointing out its basic features like the progressive role of the teacher, the learner’s subjectivity, totality, moving away from traditional evaluation and phases in the project method implementation.
Project Method as a Teaching Procedure Strategy at the University. About the effects of education and the project method
Keywords: project method; student; university teacher; training effects; The National Councils of Qualifications; phases in the project method